2017
DOI: 10.1080/09540105.2017.1350833
|View full text |Cite
|
Sign up to set email alerts
|

Production of antibodies and development of an enzyme-linked immunosorbent assay for 17β-estradiol in milk

Abstract: The residue of 17β-estradiol (E 2) in milk could potentially lead to the occurrence of various reproductive diseases; therefore, a rapid and sensitive method for monitoring E 2 residues in milk was highly necessary. In this study, we produced new polyclonal and monoclonal antibodies using E 2-3-O-carboxymethyl ether as a hapten and developed an indirect competitive enzyme-linked immunosorbent assay (icELISA) for the detection of E 2 in milk. The results showed that the sensitivity of polyclonal antibody was hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, in this work, we used the similar strategy for hapten design, but the obtained antibody seemed to be unsatisfactory (Table S1). Therefore, we used another strategy, by introducing a carboxyl group spacer from C3-OH of estriol (Bai et al, 2017). The results indicated that by using this antigen (E3-A-BSA) as immunogen, and E3-B-OVA as heterologous coating antigen, the obtained antibody showed better sensitivity in ELISA in comparison with literatures.…”
Section: Hapten Synthesis and Antibody Productionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, in this work, we used the similar strategy for hapten design, but the obtained antibody seemed to be unsatisfactory (Table S1). Therefore, we used another strategy, by introducing a carboxyl group spacer from C3-OH of estriol (Bai et al, 2017). The results indicated that by using this antigen (E3-A-BSA) as immunogen, and E3-B-OVA as heterologous coating antigen, the obtained antibody showed better sensitivity in ELISA in comparison with literatures.…”
Section: Hapten Synthesis and Antibody Productionmentioning
confidence: 95%
“…There are extracted with ethyl acetate, thin layer chromatography, high performance liquid chromatography (Gorga, Insa, Petrovic, & Barceló, 2014;Piwowarska, Radowicki, & Pachecka, 2010), gas chromatography analysis-mass spectrometry (Andrási, Helenkár, Vasanits-Zsigrai, Záray, & Molnár-Perl, 2011;Lu, Wu, Stoffella, & Chris Wilson, 2012), electroanalytical determination (Cincotto et al, 2015;Fu et al, 2016;Santos, Braga, Vieira, & Spinelli, 2010), enzyme-linked immunosorbent assay (ELISA) (Bai et al, 2017), fluoroimmunoassay (Tang, Zhao, Wu, Zhou, & Li, 2013), and immunochromatographic assay (Mukunzi et al, 2016;Wang et al, 2017) for estriol and its analogs analysis. Above all of instrument assays, chromatography spectroscopy was generally used to detect estriol in urine of pregnant women and drug.…”
Section: Introductionmentioning
confidence: 99%
“…Six to nine days after the third immunization, mouse sera were obtained by tail blood collection, and the same step was performed for subsequent immunizations. The titer and inhibition rate of each serum were detected by indirect competitive ELISA (ic-ELISA; Bai et al, 2017). For ic-ELISA, we used 10 μM ITCBE instead of PBS buffer.…”
Section: Monoclonal Antibody (Mab) Preparationmentioning
confidence: 99%
“…27,28 Accordingly, developing efficient and sensitive methods for the monitoring of E2 levels is of great significance. So far, many different techniques have been established for the determination of E2, such as gas chromatography/liquid chromatography–mass spectrometry (GC/LC-MS), 29,30 enzyme-linked immunosorbent assay (ELISA), 31,32 colorimetry, 33–35 fluorescence, 36–39 electrochemistry, 40–46 and surface-enhanced Raman spectroscopy. 47,48 Nevertheless, these methods might suffer from the high cost of devices, the need for high levels of technical skill, low sensitivity, cumbersome operation processes and the need for sample pretreatment.…”
Section: Introductionmentioning
confidence: 99%